2020
DOI: 10.3389/fimmu.2020.00102
|View full text |Cite
|
Sign up to set email alerts
|

A Tissue-Specific Rhythmic Recruitment Pattern of Leukocyte Subsets

Abstract: The circulating of leukocytes in the vasculature to reach various organs is a crucial step that allows them to perform their function. With a sequence of interaction with the endothelial cells, the leukocytes emigrate from the circulation either by firm attachment to vascular beds or by trafficking into the tissues. Recent findings reveal that the leukocyte recruitment shows time as well as tissue specificity depending on the cell type and homing location. This spatiotemporal distribution of leukocyte subsets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…However, in the study that confirmed an increased production of EV during HIV infection, the sampling was done essentially during the day [ 50 ]. Physiologically, the number of the major leukocyte subsets in blood, including neutrophils, monocytes, CD4 T cell, CD8 T cell, NK cells, and eosinophils varies throughout the day, reflecting bone marrow output and emigration from the blood into tissues [ 51 , 52 , 53 ]. This spatiotemporal distribution of leukocyte subsets is driven by the circadian expression of pro-migratory molecules expressed on the leukocytes and the endothelium [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the study that confirmed an increased production of EV during HIV infection, the sampling was done essentially during the day [ 50 ]. Physiologically, the number of the major leukocyte subsets in blood, including neutrophils, monocytes, CD4 T cell, CD8 T cell, NK cells, and eosinophils varies throughout the day, reflecting bone marrow output and emigration from the blood into tissues [ 51 , 52 , 53 ]. This spatiotemporal distribution of leukocyte subsets is driven by the circadian expression of pro-migratory molecules expressed on the leukocytes and the endothelium [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, the number of the major leukocyte subsets in blood, including neutrophils, monocytes, CD4 T cell, CD8 T cell, NK cells, and eosinophils varies throughout the day, reflecting bone marrow output and emigration from the blood into tissues [ 51 , 52 , 53 ]. This spatiotemporal distribution of leukocyte subsets is driven by the circadian expression of pro-migratory molecules expressed on the leukocytes and the endothelium [ 52 , 53 ]. Systemic circadian signals and cell-intrinsic molecule clocks contribute to the oscillatory expression of these pro-migratory molecules [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that leukocyte trafficking follows a circadian oscillation [reviewed extensively in (3,4,25)]. The expression of circadian clock genes is ubiquitous to nearly all immune cells, and clocks can directly regulate immune cell trafficking.…”
Section: Circadian Regulation Of Leukocyte Trafficking In Ageingmentioning
confidence: 99%
“…Due to the complexity and universality of the circadian rhythm system, the study of its molecular mechanism is challenging. Although increasing evidence suggests that circadian dysregulation affects the immune system [14,15], the exact mechanism of the interaction between miRNAs, clock genes, and glioma progression remains unclear.…”
Section: Introductionmentioning
confidence: 99%